The production of capitalist urban space: contributions of functionalism, the School of Chicago, Henri Lefebvre and Manuel Castells - L'Huillier, Francisco José (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article examines the main theoretical debates that have been constituted from the social sciences around the process of space production in capitalist cities between the beginning of the 20th century and the seventies decade, putting into perspective both their contributions and their limitations in the light of recent debates on the urban question. Although the authors and currents of thought that have addressed these objects of study are certainly numerous, only a small group is reviewed: functionalist urbanism, the Chicago School, and critical urban sociology (with Henri Lefebvre and Manuel Castells), since these theoretical incursions are the most prominent in the attempt to elaborate a comprehensive reflection on the urban question. From the analysis of the literature and the most representative conceptualizations of each one of these currents, it is evident that their formulations respond closely to the historical context in which they emerge, making explicit in them a particular articulation between space, politics and society. Thus, it is demonstrated how functionalist urbanism and the Chicago School emerge in order to problematize and restructure, at the level of urban practice, the socio-spatial imbalances of the process of urbanization of the late 19th and early 20th centuries, while critical urban sociology questions the set of premises held by those pioneer schools, for which it will delve into the study of the class dynamics or conflicts that conceal the process of production of space.